2012
DOI: 10.1128/aem.00218-12
|View full text |Cite
|
Sign up to set email alerts
|

Expression of the Laccase Gene from a White Rot Fungus in Pichia pastoris Can Enhance the Resistance of This Yeast to H 2 O 2 -Mediated Oxidative Stress by Stimulating the Glutathione-Based Antioxidative System

Abstract: ABSTRACTLaccase is a copper-containing polyphenol oxidase that has great potential in industrial and biotechnological applications. Previous research has suggested that fungal laccase may be involved in the defense against oxidative stress, but there is little direct evidence supporting this hypothesis, and the mechanism by which laccase protects cells from oxidative stress also remains unclear. Here, we report that the expression of the laccase gene from white rot fungus in Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
47
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 77 publications
(47 citation statements)
references
References 62 publications
(68 reference statements)
0
47
0
Order By: Relevance
“…The change in antioxidative redox state caused by Bordeaux mixture may also contribute to increased laccase production by B. bassiana . In fact, enhanced laccase activity or laccase gene expression was previously found to be part of the response system to oxidative stress conditions in several white‐rot fungus species . Similarly, in entomopathogenic fungus M. anisopliae , the involvement of laccase in fungal tolerance to environmental stresses has been reported …”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The change in antioxidative redox state caused by Bordeaux mixture may also contribute to increased laccase production by B. bassiana . In fact, enhanced laccase activity or laccase gene expression was previously found to be part of the response system to oxidative stress conditions in several white‐rot fungus species . Similarly, in entomopathogenic fungus M. anisopliae , the involvement of laccase in fungal tolerance to environmental stresses has been reported …”
Section: Discussionmentioning
confidence: 86%
“…In fact, enhanced laccase activity or laccase gene expression was previously found to be part of the response system to oxidative stress conditions in several white-rot fungus species. 49,50 Similarly, in entomopathogenic fungus M. anisopliae, the involvement of laccase in fungal tolerance to environmental stresses has been reported. 18 In conclusion, the results indicated that Bordeaux mixture caused hazardous effects in B. bassiana, which was probably related to its heavy metal component -copper.…”
Section: Discussionmentioning
confidence: 89%
“…Research has suggested that overproduction of laccase during interspecific interaction is caused 16 by oxidative stress, which involves a series of competitive and defensive mechanisms (Jaszek et 17 al., 2006;Li et al, 2011;Yang et al, 2012). To determine oxidative stress during mycelial 18 interaction, we used Nitroblue tetrazolium (NBT) to stain the mycelium in both interaction zones 19 and single species ( Figure 1D DsPo, which could indicate much higher accumulation of ROS during mycelial interactions.…”
Section: Assays Of Laccase 16mentioning
confidence: 99%
“…Considering that laccase is the most important oxidative enzyme secreted 5 from white rot fungi, many studies focused on the laccase induction particularly in the mycelial 6 interaction of different fungi (Baldrian, 2004;Flores et al, 2009;Kuhar et al, 2015;Wei et al, 7 2010), but lacking further exploration on the molecular mechanism of interspecific interaction and 8 laccase induction among different fungi. As oxidative stress can occur in the interaction region of 9 different fungi (Silar, 2005), and fungal laccase can be involved in the defense response to 10 oxidative stress, which is also commonly accompanied by the overexpression of a large amount of 11 other antioxidative enzymes (Jaszek et al, 2006;Yang et al, 2012). Thus, in this study, we 12 performed a transcriptional analysis of gene expression changes in D. squalens under the 13 interaction with two wood-decaying fungi T. versicolor and P. ostreatus to investigate the 14 mechanism of fungal competitive interaction, and focus on the potential role including resistance 15 against oxidative stress that laccase played during the interaction of D. squalens with other two 16 competitors based on analysis of transcriptomic level.…”
mentioning
confidence: 99%
“…Farnesol, thus, acts as an intercellular adaptive signal that confers oxidative stress resistance to the cells within the same population, and H 2 O 2 participates in the farnesol signaling pathway [28]. Farnesol also induced ROS production in bacterial species and other fungal species [29,30]. This is the first time it has been demonstrated that farnesol can induce ROS production in T. versicolor.…”
Section: Farnesol Increases Lac Gene Expressionmentioning
confidence: 99%